2007
DOI: 10.2174/156800907783220435
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Action of Citrus Flavonoids on Multiple Cancer-Related Biological Pathways

Abstract: Attempts to control cancer involve a variety of means, including the use of suppressing, blocking and transforming agents. Suppressing agents prevent the formation of new cancers from pro-carcinogens, blocking agents prevent carcinogenic compounds from reaching critical initiation sites, while transformation agents act to facilitate the metabolism of carcinogenic components into less toxic materials or to prevent their biological actions. Flavonoids can act as all three types of agent. Epidemiological and anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 92 publications
1
13
0
Order By: Relevance
“…It has been suggested that flavonoids-rich diet has an adverse effect on the proliferation of cancer cells [94,95].Various mechanisms have been proposed to explain the anti-proliferative activity of flavonoids, for example, it has been proposed that the anti-proliferative effects of flavonoids are mainly mediated by the inhibition on several kinases and kinase inhibitors involved in cellcycle arrest and apoptosis [85]. Cyclin-dependent kinases (CDKs) have been recognized as key regulators of cell cycle progression.…”
Section: Anti-proliferationmentioning
confidence: 99%
“…It has been suggested that flavonoids-rich diet has an adverse effect on the proliferation of cancer cells [94,95].Various mechanisms have been proposed to explain the anti-proliferative activity of flavonoids, for example, it has been proposed that the anti-proliferative effects of flavonoids are mainly mediated by the inhibition on several kinases and kinase inhibitors involved in cellcycle arrest and apoptosis [85]. Cyclin-dependent kinases (CDKs) have been recognized as key regulators of cell cycle progression.…”
Section: Anti-proliferationmentioning
confidence: 99%
“…Targeting AKT-p53 network through RARγ may provide a new therapeutic method. Since flavonoids represent a large class of naturally occurring active compounds contained in food and medicinal plants 21 and have been shown to have potential to combat HCC 42 . Our findings suggest that RARγ-based optimized flavonoid leads may help generate improved anti-HCC drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids, abundant in many plant species including fruit and vegetables, are excellent leads for drug development 21 . Acacetin (5,7-dihydroxy-4′-methoxyflavone), a flavonoid compound isolated from Flos Chrysanthemi Indici , has been shown to have anticancer activity against various malignancies, such as lung cancer, breast cancer and prostate cancer 2224 , indicating its potential clinical value in cancer treatment 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacology of citrus peels: Citrus fruits are commonly known for their uses in the field of culinary and even medical. Hesperidin, narigin, nobilentin, tangeretin, neoponcirin, narirutin and diosmin among others are common flavonoids naturally abundant in citrus [24][25][26]. In this review, common flavonoids from citrus peel are being bibliographically studied on their pharmacological potentials.…”
mentioning
confidence: 99%
“…Though the natural content of 5-demethylated polymethoxyflavones in citrus peels is low, it has been confirmed that they have higher potency in combating diseases than their non-demethylated counterparts [27,28]. A number of reports have demonstrated the biological properties of these citrus flavonoids including anticarcinogenic, antidiarrheal, antihypocholesterolemic, antiobesity, antidiabetic, antioxidant and anti-inflammatory properties, which help in enhancing human health [24][25][26][27][28][29].…”
mentioning
confidence: 99%